2021
DOI: 10.3389/fgene.2021.728526
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association of Proprotein Convertase Subtilisin/Kexin Type 9 Plasma Levels in the ELSA-Brasil Study

Abstract: Pharmacological inhibition of PCSK9 (proprotein convertase subtilisin/kexin type 9) is an established therapeutic option to treat hypercholesterolemia, and plasma PCSK9 levels have been implicated in cardiovascular disease incidence. A number of genetic variants within the PCSK9 gene locus have been shown to modulate PCSK9 levels, but these only explain a very small percentage of the overall PCSK9 interindividual variation. Here we present data on the genetic association structure between PCSK9 levels and geno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Genomic DNA extraction has been previously described [ 8 ]. SaMi-Trop DNA samples were genotyped using two different genotyping arrays: Axiom_PMRA.r3 array (N = 2,606) or the Axiom_sarscov array (N = 792) (ThermoFisher, Waltham, USA) and genotypes annotated using the array specific annotation file provided at the ThermoFisher website.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA extraction has been previously described [ 8 ]. SaMi-Trop DNA samples were genotyped using two different genotyping arrays: Axiom_PMRA.r3 array (N = 2,606) or the Axiom_sarscov array (N = 792) (ThermoFisher, Waltham, USA) and genotypes annotated using the array specific annotation file provided at the ThermoFisher website.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the previously described GWAS study that associates an SNP affecting an RSUME’s QTL with cardioembolic stroke ( 19 ) provides a novel view for the hypoxia-mediated regulation of RSUME expression in cardiac tissue. Moreover, a different study found a suggestive locus near the RSUME gene that is involved in inter-individual levels of the Proprotein convertase subtilisin/kexin type 9 (PCSK9), which is a regulator of LDL receptor degradation and is associated with cardiovascular risk ( 45 ). Although the incidence of congenital heart defects is high, only a reduced number of them are caused by Mendelian inheritance ( 46 ).…”
Section: Rsume As a Biomodulator In Developmentmentioning
confidence: 99%